Caregivers’ perspectives on factors influencing adolescent girls’ engagement in sexual risk-taking in Uganda: A qualitative study - Ozge Sensoy Bahar; Fred M. Ssewamala; Flavia Namuwonge; Florence Namuli; Proscovia Nabunya (PLoS ONE, 2025)
Sub-Saharan Africa is home to two-thirds of people living with HIV globally, and women and girls (all ages) account for 62% of all new HIV infections in the region. Sexual risk-taking puts adolescent girls at risk for adverse health outcomes, including HIV/AIDS. Caregivers’ beliefs about adolescent sexual risk-taking have implications for how and when they would discuss this topic with their children. In this study, we conducted semi-structured in-depth interviews with 58 caregivers of adolescent girls to explore their perspectives on factors that influence adolescent girls’ decisions to engage in sexual risk-taking in Uganda. We employed a thematic analysis approach, combining both inductive and deductive methods to analyze the data. A range of protective and risk factors was identified across personal, proximal, and distal contexts. At the personal level, future goals, concerns about negative health consequences, religiosity, temperament, and puberty were identified as contributing factors. At the proximal level, family and peer-related factors were mentioned. At the distal level, poverty and program counseling were discussed. Study results point to the need for combination interventions that include both caregivers and their daughters to reduce sexual risk-taking among adolescent girls in Uganda.